Crabs Identification in the Aek Sidempula River, Pearung Silali Village Paranginan District North Sumatera Province. - Krisna Mailin Simanjuntak; Windarti '; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Aek Sidempula River, a small river that has high quality water and it is inhabitedby aquatic organisms such as crabs. Scientific information on crabs living in thatarea, however, is almost none. To understand the crabs present in that river, astudy has been conducted from November 2015 to January 2016. The crabs wascaptured using traditional line fishing. Morphometrical and meristicalcharacteristics on the crabs captured were described based on Ng dan Tan (1998)and Ng and Takeda (1992). The crabs sampled were only 40 crabs, and they werebelonged to a single species namely Malayopotamon tobaense (Potamidae). Thisspecies is medium sized crab, 16 – 49 mm carapace width, with dark purplecarapace. This species is characterized by the presence of first gonopod that hasupward turned tip. Male has bigger chelae and narrower abdomen than that of thefemale.Keywords: Crabs, Potamidae, Malayopotamon tobaense, Aek SidempulaRiver, Pearung Silali, North Sumatera.